(untitled) (The International Journal for Scientific Research, 2025)
This study investigates the correlation between the (Human Energy Field) and the phenomenon of (Synesthesia), emphasizing their combined impact on (Sensory Perception) and the processes underlying artistic creativity, particularly within the domains of (Visual Arts) and (Music). The research provides a comprehensive overview of the conceptual evolution of (Cosmic Energy), tracing its roots from ancient philosophical traditions to contemporary scientific inquiries conducted in the United States, Japan, and Russia. Special attention is given to the constructs of (Aura) and (Chakras) as central components of the human energetic system. The phenomenon of (Synesthesia) is examined in relation to distinct neurocognitive patterns that enable some individuals to experience multi-sensory integration—such as perceiving sounds as colors or associating visual stimuli with tactile sensations—thereby enhancing their expressive and interpretative capacities. Furthermore, the study presents an empirical investigation conducted with university students, integrating structured art-making sessions accompanied by musical compositions to observe and analyze affective and sensory interactions, and to identify potential indicators of (Sensory Crossover). The findings underscore the significance of (Bioenergy) as a potentially influential variable in artistic expression and emotional healing. The research advocates for further interdisciplinary exploration into these phenomena to advance theoretical and practical understanding of their implications in creative and psychotherapeutic contexts.